Effectiveness of Transformative Green Economy in Biology (T-GEB) Learning Model on Changing Students' Conservation Perceptions about Elaeis guineensis Jacq. in Ecology and Socio-Economics - Mandandari, Delia; Suwono, Hadi; Fachrunnisa, Rifka (BIOEDUKASI, 2024)
Changing perceptions regarding the importance of conservation can be an effort to increase conservation awareness which is still low in society. This research aims to determine the effectiveness of implementing the Transformative Green Economy in Biology (T-GEB) Learning Model in changing students' perceptions of conservation. The sample for this research is class X students of State Senior High School 1 Turen for the 2022/2023 academic year. The type of quantitative research is pre-experimental using pretest-posttest and questionnaires, while qualitative data collection uses reflective essays. The application of the T-GEB Learning Model shows that learning is quite effective in improving students' cognitive learning outcomes, with an N-Gain Score of 58% on biodiversity material and 6.4% on environmental change material. the application of the T-GEB model can change students' perceptions of conservation from previously having a strong percentage of 77.7% to 91.3% which is classified as very strong based on the results of the conservation awareness questionnaire. Changes in students' perceptions of conservation are also supported by the results of reflective essays, with three themes formed, namely awareness of the important role of oil palm, perception of the impact of oil palm expansion, and awareness of conservation through oil palm expansion.